2013
DOI: 10.4103/0974-8520.127717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Bilvadileha in the management of irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common conditions encountered in clinical practice but one of the least well understood. Symptoms of this disorder are chronic, sometimes severe and often respond poorly to treatment, resulting in reduced quality of life. There is no specific test for IBS, although diagnostic tests may be performed to rule out other problems. In present clinical trial 51 patients of IBS were registered out of which 46 patients completed the treatment. Bilvadileha was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…All bothersome symptoms should be targeted while treating these patients rather than only the predominant symptoms as suggested earlier taking into account specific IBS subtypes, symptom severity and contributing factors including psychosocial and dietary issues [63]. IBS patients with low symptom load do find significant improvement in their symptoms by use of antispasmodics [110,111], bulking agents, antidiarrheals [112,113], pro-motility agents including laxatives, [114,115] and low-FODMAP diet [42]. An outline of the management of IBS is summarized in Fig.…”
Section: Statement 20: the Initial Treatment Of Ibs Is Primarily Symp...mentioning
confidence: 99%
See 1 more Smart Citation
“…All bothersome symptoms should be targeted while treating these patients rather than only the predominant symptoms as suggested earlier taking into account specific IBS subtypes, symptom severity and contributing factors including psychosocial and dietary issues [63]. IBS patients with low symptom load do find significant improvement in their symptoms by use of antispasmodics [110,111], bulking agents, antidiarrheals [112,113], pro-motility agents including laxatives, [114,115] and low-FODMAP diet [42]. An outline of the management of IBS is summarized in Fig.…”
Section: Statement 20: the Initial Treatment Of Ibs Is Primarily Symp...mentioning
confidence: 99%
“…Hence, these drugs must be used with caution. Table 7 summarizes some of the studies from India on different antispasmodic drugs in the management of IBS [110,111,122,123].…”
Section: Statement 21mentioning
confidence: 99%
“…The sangrahi characteristic of bilva is highly helpful in reducingslough and pus discharge. In addition to Bilva (Aegle marmelos), Prakshepa Dravyas in Bilvadileha include Dhanyaka ( Coriandrum sativum ) , Jiraka ( Cuminum cyminum ), Ela ( Elettaria cardamomum ), Keshara ( Crocus sativus ) , Twak ( Cinnamomum zeylanicum ) , Trikatu, Musta ( Cyperus rotundus ), and they possess such attributes as deepana, pachaka, kaphahara, vedanasthapak, and rasayana [ 21 ]. Complex medications used in ayurvedic medicine are based on the principles of antagonistic and synergistic interactions to produce the desired effects.Saptavimshati guggulu mentioned in Yogaratnakara, Bhaishajya Ratnavali and Chakradatta is widely indicated in Dusta vrana and Bhagandhara and helps in wound healing and achieving healthy granulation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…in 4 HMs were also noted ( Posadzki et al, 2013 ). Diverse different traditional medicines such as Korean medicine ( Ko et al, 2013 ), traditional Chinese medicine ( Zheng et al, 2021 ), Persian medicine ( Amini-Behbahani et al, 2019 ), Kampo (traditional Japanese herbal medicine) ( Oka et al, 2014 ) and Ayurveda ( Tiwari et al, 2013 ) reported the efficacy and safety of HM in IBS. These results are important for the discovery and development of new treatments for IBS.…”
Section: Discussionmentioning
confidence: 99%